Free Testosterone Level Correlated with the Metabolic Abnormalities Dependent on Central Obesity in Women with Polycystic Ovary Syndrome - Dong, Z.; Chen, X.; Li, L.; Huang, J.; Yin, Q.; Yang, D. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Women with polycystic ovary syndrome (PCOS) have increased risks of developing metabolic abnormalities compared with the women without PCOS. Hyperandrogenemia is one of the most important characteristics of PCOS. However, the correlations between hyperandrogenemia and metabolic disorders are uncertain.To elucidate the relationship between androgen indices and metabolic abnormalities in Chinese women with PCOS.A retrospective analysis of the anthropometric and biochemical records of 408 women with PCOS.The prevalence of metabolic syndrome (MetS) was 15.7% in women with PCOS. No association existed between total testosterone (TT) and metabolic profile. Free testosterone (FT) correlated with most of the metabolic variables by unadjusted correlation analyses. The women with elevated FT levels exhibited more unfavorable metabolic profiles compared with the women with normal FT levels. After adjusting for the confounding factors by multivariate logistic regression analysis, the women with elevated FT levels had higher prevalence of central obesity than the women with normal FT levels (odds ratio [OR] 2.346, p=0.042). Women with reduced sex hormone-binding globulin levels were more likely to have central obesity, overweight, raised fasting glucose, insulin resistance, and raised diastolic blood pressure. Raised dehydroepiandrosterone sulfate (DHEAS) level was associated with a lower probability of having central obesity (OR 0.293, p=0.001) and overweight (OR 0.47, p=0.023).FT has closer association with metabolic parameters than TT. FT can involve in the development of metabolic disorders dependent on central obesity. Raised DHEAS level can reduce the risks of central obesity and overweight.
Keywords: polycystic ovary syndrome; androgens; free testosterone; metabolic abnormalities; central obesity